Analysis of Financial Literacy Publications Using Bibliometric Computation with Vosviewer Assistance - Muhammad Ismail; Wahyu Wahyu; Hisny Fajrussalam (Jurnal Pendidikan Terapan, 2026)
Purpose: This study aims to analyze the trends, development, and characteristics of global scientific publications on financial literacy over a ten-year period (2014-2024) to address the limited availability of systematic scientific mapping using computational bibliometric approaches in this field. Methods: The research utilized a quantitative bibliometric design, collecting metadata from 990 financial literacy articles indexed in Google Scholar via Harzing’s Publish or Perish application. Data processing was conducted using Microsoft Excel, followed by computational mapping and network, density, and overlay visualization analysis using the VOSviewer application to examine co-citations and term relationships. Findings: The analysis revealed 990 publications with an unstable trend, peaking at 146 articles in 2023 and dropping to 115 in 2024, yielding 45,838 total citations, an h-index of 100, a g-index of 170, and an average of 2.59 authors per article. VOSviewer mapping identified 13 interconnected keyword clusters where "financial literacy," "role," and "analysis" form the highest density core, while emerging topics include financial technology, financial inclusion, and COVID-19. Research Implications: These findings provide a comprehensive reference for researchers to determine future research directions, specifically highlighting applied issues driven by social and technological changes, and offer stakeholders a foundation for integrating financial literacy into elementary school learning and educator roles. Originality: The study contributes a distinct ten-year computational mapping of financial literacy publications, successfully uncovering under-researched gaps such as the role of school counselors and high school teachers within the discipline.